Return the night - Chan, Chanel Jia Lun (Nanyang Technological University, 2021)
The paper reflects the journey as a production designer working on Return The Night. Return The Night is a short film revolving Xu Xin who finds out she was raped the night before. The film explore Xu Xin's inner psyche and emotions in response to such a traumatic event. Through the perspective of a production designer, the paper highlights key creative processes that led to the worldbuilding of the film.